Constructivists’ Didactics in Teaching Technology Education in Ethiopian Technology Universty- Practices and Challenges (The Case of Adama Science and Technology University) - Engdasew, Ziyn (Richtmann Publishing, 2013)
The present study has been intended to assess the applicability of didactics of constructivism in the instructional process oftechnology education and identifying the prominent constraints that hinder the implementation of constructivist didactics intechnological education classes. A descriptive survey research methodology was designed in order to attain the purpose.Simple random sampling and availability sampling techniques were utilized to select sample from the study site. Accordingly,42 teachers and 147 students were selected from four technology education departments. The data were collected throughquestionnaire and observations. The analysis of quantitative data was made by descriptive statistics like frequency counts,percentage, t-test, and Ch-squire test.The result of the study revealed that most of technology education instructors neitherundertake prior skill analysis nor attempted to integrate prior knowledge and skill lessons in their daily class lesson. Moreover,technology instructors are not enthusiastic to engage students to discover a new skill and apply in to practice. Diverse and goalfree evaluation techniques were not employed to assess the skill mastery level of students. Furthermore, the research hasshown that in availability of facilities, and diversity of student interest and lack of teachers training in modern techno- pedagogyfound to be the major challenges in the practicality of constructivist didactics in technology education. Thus, it can beconcluded that the major challenges in the utilisation of constructivist approach in teaching technology education are shortageof the required facilities and trainings. Therefore, it was recommended that the university should have to fulfil the requiredfacilities and design specific and peculiar professional development programmes in order to acquaint instructors with moderninstructional skills and techniques of technology education.